From rupture to recovery: A case report on a multidisciplinary approach to arteriovenous malformation (AVM)-associated intracerebral hemorrhage - Ibrahim Khalil, MBBS; Md. Imran Hossain, MBBS; Mahmuda Akter, MBBS (Radiology Case Reports)
Arteriovenous malformations (AVMs) are rare congenital vascular anomalies that increase the risk of severe complications, such as intracerebral hemorrhage (ICH), necessitating complex, multidisciplinary management. This case report describes the successful treatment of a 30-year-old male who presented to the emergency department with an acute, severe headache, nausea, and neurological deficits due to a ruptured AVM causing ICH. Initial neuroimaging revealed a significant right parietal lobe hemorrhage, and digital subtraction angiography (DSA) confirmed a Spetzler-Martin Grade II AVM, indicating moderate surgical complexity; the patient underwent staged interventions, starting with endovascular embolization using the Onyx liquid embolic system to reduce nidus perfusion, followed by microsurgical resection with intraoperative neuromonitoring, resulting in complete AVM removal and near-normal neurological recovery at discharge. The integration of neurosurgery, interventional radiology, and neuro-anesthesiology expertise facilitated a tailored approach, leveraging advanced imaging and therapeutic techniques to minimize procedural risks and optimize outcomes. This case highlights the importance of early diagnosis, precise imaging with tools like DSA, and a collaborative, staged treatment strategy in achieving favorable results in AVM-associated ICH. It also emphasizes the value of personalized care plans and continuous postoperative follow-up to ensure long-term success and detect potential recurrence. Lessons learned include the efficacy of combining embolization and resection for moderate-complexity AVMs and the need for ongoing research to refine protocols and improve prognosis, reinforcing that multidisciplinary coordination is essential for managing such intricate vascular anomalies effectively.